Host cell and EBNA-2 regulation of Epstein-Barr virus latent-cycle promoter activity in B lymphocytes. - Rooney, C M (1992)
The six latent-cycle nuclear antigens (EBNAs) of Epstein-Barr virus (EBV), whose genes share 5' leader exons and two promoters (Cp and Wp), are differentially expressed by cells of the B lineage. To examine the possibility that EBNA gene expression is regulated through selective use of Cp and Wp, we monitored the activity of promoter-chloramphenicol acetyltransferase (CAT) gene constructs transfected into EBV-positive and EBV-negative B lymphocytes and Burkitt's lymphoma cells. Wp was a much stronger promoter than Cp in EBV genome-negative B-cell lines and was used exclusively in primary B cells. When B cells were infected with transforming EBV, Cp became the stronger promoter. This switch was not observed when B cells were infected with an immortalization-deficient virus, P3HR-1, which lacks the EBNA-2 open reading frame and expresses a mutant leader protein (EBNA-LP). Cp function was transactivated when EBV-negative or P3HR-1-infected B cells were cotransfected with Cp and a 12-kb fragment of DNA (BamHI-WWYH) that spanned the P3HR-1 deletion. This activity was mapped to the EBNA-2 gene within WWYH; constructs expressing EBNA-LP did not induce Cp function, and the deletion of 405 bp from the EBNA-2 open reading frame abolished transactivation. This research demonstrates host cell and EBNA-2 regulation of latent-cycle promoter activity in B lymphocytes, a mechanism with implications for persistence of EBV-infected lymphoid cells in vivo.